Canada and our Latin-American neighbors - Bruner, Herbert Bascom, 1892-1974 (Laidlaw history series., 1968)
A social studies text which examines briefly the history, geography, resources, civilization and ways of life of Canada, Mexico, Central America, the Caribbean, and South America, with study questions and bibliographies.